Integrasi Metode Failure Mode and Effect Analysis (FMEA) Berbasis Eco-Severity guna Mitigasi Risiko Kecacatan dan Pemborosan Material pada UMKM Perkayuan - Rudi Kurniawan (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
The Indonesian woodworking MSME sector faces systemic challenges in the form of wood material variability fluctuations in moisture content, fiber heterogeneity, and non-uniform density which directly trigger product defects and the accumulation of unproductive solid waste. This study implemented a modified Failure Mode and Effect Analysis (FMEA) method with the integration of Eco-Severity variables: severity weighting that not only measures functional and financial impacts but also explicitly considers the volume of scrap material generated from each failure mode. The case study was conducted at a Wooden Bracket Manufacturing MSME in Pasuruan, East Java, with three months of production data (total 2,500 units, total defects 185 units or 7.4%). Pareto analysis identified two dominant types of defects: Oblique Drill Holes (48.1% of total defects, n=89) and Wood Cracks/Splitting during Clamping (28.6%, n=53), which cumulatively accounted for 76.7% of all defects. The Eco-Severity Based FMEA Matrix places the Drilling Station as the highest risk locus with a Risk Priority Number (RPN) of 336 (S=8, O=7, D=6), followed by the Cutting Station with an RPN of 210 (S=7, O=6, D=5). The accumulation of solid wood waste due to both failure modes is estimated to reach 23.95 kg in three months of observation.